(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Single crystals are the fundamental building blocks for modern technology. The study of growth and characterization of single crystals is forming in backbone of modern scientific developments and also is receiving increasing importance due to their number of applications in solid state technology. These technical advantages have been accompanied by rapid strides in crystal growth. The modern technological developments depend greatly on the availability of suitable single crystals, whether it is for lasers, semiconductor, magnetic devices, superconductors, telecommunication. Crystals grow plays an important role in coming years of science and technology the crystal form by these technique are pure and perfect crystals in bulk. The production of laser crystals to ruby sapphire NOYAG and Non-linear crystal in field of solid state physics and electronic as well as in photonics which are based on crystal growth revolution. For technological advancement in the recent year we are in early step with respect to some important crystals such as Gallium, Nitride, Diamond and Silicon Carbide. Single crystals may field extensive application in field of conversion of solar energy information storage and manipulation on large capacity digital computer improves.